2022
DOI: 10.5194/acp-22-465-2022
|View full text |Cite
|
Sign up to set email alerts
|

Measurement report: Particle-size-dependent fluorescence properties of water-soluble organic compounds (WSOCs) and their atmospheric implications for the aging of WSOCs

Abstract: Abstract. Water-soluble organic compounds (WSOCs) play important roles in atmospheric particle formation, migration, and transformation processes. Size-segregated atmospheric particles were collected in a rural area of Beijing. Three-dimensional fluorescence spectroscopy was used to investigate the optical properties of WSOCs as a means of inferring information about their atmospheric sources. Sophisticated analysis on fluorescence data was performed to characteristically estimate the connections among particl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 76 publications
(103 reference statements)
2
8
0
Order By: Relevance
“…The peaks of EEM spectra of HULIS coincided with those of WSOC reported in our previous research , with their fluorescence peaks mainly produced at regions II–V. The fluorescence efficiency (represented by AFI/TOC) of HULIS was higher than that of WSOC with AFI/TOC HULIS being 1.34 times of AFI/TOC WSOC in winter and 1.08 times in summer.…”
Section: Resultssupporting
confidence: 84%
“…The peaks of EEM spectra of HULIS coincided with those of WSOC reported in our previous research , with their fluorescence peaks mainly produced at regions II–V. The fluorescence efficiency (represented by AFI/TOC) of HULIS was higher than that of WSOC with AFI/TOC HULIS being 1.34 times of AFI/TOC WSOC in winter and 1.08 times in summer.…”
Section: Resultssupporting
confidence: 84%
“…The maximum wavelength intensity of the spectra from the winter and summer samples ranged from 440 to 464 nm and 439-449 nm, respectively. Similar ranges have been reported by other researchers for highly oxygenated carbonaceous and humic-like substances (HULIS) (McKnight et al, 2001;Chen et al, 2016b;Qin et al, 2021). Barsotti et al (2016) reported that HULIS derived from the oligomerization of phenolic compounds exhibited a strong fluorescence emission in the vicinity of 450 nm.…”
Section: Analysis Of Pm 25 By Fluorescence Spectroscopysupporting
confidence: 87%
“…Similarly, the measurements in Beijing, China showed that HULIS was rich in fine particles and protein-like compounds were rich in coarse particles (J. Qin et al, 2022). The results by Wu et al (2020) showed a monomodal size distribution of BrC absorption in winter with a peak in the fine mode (<2.1 μm) but a bimodal distribution in summer with two peaks in the fine and coarse modes.…”
Section: Implications From Ambient Samplesmentioning
confidence: 69%